2022
DOI: 10.1136/annrheumdis-2021-220750
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in patients with early rheumatoid arthritis undergoing treat-to-target therapy: predictors and response to treatment

Abstract: ObjectivesFatigue is a frequent symptom in rheumatoid arthritis (RA) and has high impact on quality of life. We explored associations between disease activity and fatigue in patients with early RA during the initial 24 months of modern treat-to-target therapy and predictors of fatigue after 24 months of follow-up.MethodsData were obtained from the treat-to-target, tight control Aiming for Remission in Rheumatoid Arthritis: a Randomised Trial Examining the Benefit of Ultrasound in a Clinical Tight Control Regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Strikingly though, a higher baseline swollen joint count predicted lower long-term fatigue. These findings add to the recent results of the ARCTIC trial (Aiming for Remission in rheumatoid arthritis: a randomised trial examining the benefit of ultrasound in a Clinical TIght Control regimen), in which more swollen joints and higher ultrasound inflammation at baseline were associated with less fatigue at year 2, while a predisposing effect was seen for PGA 50. Together, the results of both trials could indicate that RA-related fatigue is a composite of inflammation-driven fatigue and fatigue with a stronger psychosocial background.…”
Section: Discussionsupporting
confidence: 57%
“…Strikingly though, a higher baseline swollen joint count predicted lower long-term fatigue. These findings add to the recent results of the ARCTIC trial (Aiming for Remission in rheumatoid arthritis: a randomised trial examining the benefit of ultrasound in a Clinical TIght Control regimen), in which more swollen joints and higher ultrasound inflammation at baseline were associated with less fatigue at year 2, while a predisposing effect was seen for PGA 50. Together, the results of both trials could indicate that RA-related fatigue is a composite of inflammation-driven fatigue and fatigue with a stronger psychosocial background.…”
Section: Discussionsupporting
confidence: 57%
“…Singh et al (2014), reported that fatigue scores are significantly and positively associated with the DAS28, CDIA, TJC, SJC, PGA, and EGA [ 73 ]. Holten et al (2021) found that a high number of RA patients suffer from fatigue (69%) and that this high prevalence decreased during treatment in association with PGA and SJC [ 74 ]. Many people with RA (up to 43%) show a somatization comorbidity phenotype (the PS symptoms measured in our study) and the response to treatment may be reduced in this group of patients [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is one of the symptoms of rheumatoid arthritis. It is noted in more than 70 percent of patients [ 6 ]. Although it is a subjective symptom that also depends on many factors unrelated to the disease, it has a significant impact on the patient’s well-being and functioning, and is associated.…”
Section: Introductionmentioning
confidence: 99%